Penerapan Etika PNS Dalam Pelaksanaan Tugas Aparatur Pelayanan Publik (Suatu Studi di Kantor Camat Wanea Kota Manado) - Santiarsti, Thea; Dengo, Salmin; Ruru, Joorie (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: Government Regulation 42 of 2004 on Life Coaching Corps and the Code of Conduct for civil servants, explicitly and clearly stated ethical obligation for civil servants in carrying out official duties. But in reality there is still the attitude and behavior of civil servants that do not fit. This research is to answer the question "to what extent the application of ethics of civil servants in the discharge of public service personnel in the sub-district office Wanea Manado.Research using qualitative methods. In this case the application of ethics of civil servants visits of eight indicators: (1) carry out the duties and powers according to the provisions; (2) establishing a work ethic to improve performance; (3) comply with and adhere to operational standards and obedient labor; (4) ensuring cooperatively work in realizing the efficiency and effectiveness; (5) sought to develop competencies and creative and innovative thinking in the implementation of tasks; (6) accountable in carrying out the task; (7) responsive, open, honest, and accurate, and timely in completing tasks; (8) use of resources in an efficient and effective organization; Informants in this study were officials and staff at Head Office Wanea, as many as 10 people. Data collection by interview; while data analysis using interactive model analysis techniques of Miles and Hubernann.The results showed that the application of ethics of civil servants of eight indicators that can be applied to everything is pretty well by the public service personnel in the sub-district office Wanea, but not optimal.Based on the results of these studies conclude that the application of ethics of civil servants specified in the PP. No. 42 of 2004 has not been optimally performed by the apparatus of public services in the sub-district office Wanea Manado, but generally has been good enough. Based on the conclusions of the research results can be put forward suggestions to improve the application of ethics among civil servants in the public service apparatus, as follows: (1) need more intensive socialization of the PP. 42 of 2004 to the whole apparatus of public services (2) enforcement of civil etika needs to be improved by implementing a consistent and objective sanctions against any ethics violations.Keywords: Application, Ethics, Public Service.